Trend Analysis of Indonesian Migrant Worker Profiles: Redirecting Strategy on Indonesia’s Demographic Bonus - Dina Eka Putri; Mega Nisfa Makhroja (Department of International Relations, University of Mataram, 2023)
Indonesian migrant workers (IMW) make a significant impact not only for themselves, but also for their families, and country’s economy. The top destinations for PMI include Malaysia, Saudi Arabia, Hong Kong, Taiwan, and Singapore, where they find employment in various sectors. However, Indonesia is entering a demographic bonus era, characterized by a large proportion of the population being in the working-age group. This demographic shift presents opportunities for economic growth, job creation, and increased productivity if effectively managed. Meanwhile, the rise of ageing population in several developed countries open more opportunities for PMI. Using a mixed-methods approach, with push full migration, population trend and aging population analysis, this study aims to analyze the evolving trends in PMI profiles and reassess their position in the international labor market. The study highlights the importance of understanding the changing patterns and identifying Indonesia's current positioning to devise effective strategies for PMI. The study findings indicate that the characteristics of PMI have become more diverse and cannot be represented only by one single profile. Based on the analysis, Indonesia has the potential to unlock its workforce potential, drive economic growth, and establish mutually beneficial partnerships by capitalizing on the demographic bonus. Strategic leveraging of this advantage and optimizing opportunities in the international labor market can facilitate Indonesia's economic development while prioritizing the well-being of its migrant workers.